Domestic Enterprises in Supply Chains of Multinational Corporations: Vietnam Case Study - Lam Si Tran; Ngoc ThiBich Tran; Galina Anzelmovna Barysheva; Binh Thanh Dao; Trung Duc Tran (International Journal of Supply Chain Management, 2020)
Abstract—Vietnam’s international integration has also changed rapidly with the trend of gradually entering the global supply chain (GSC) and global value chain (GVC) that help create a powerful dynamic for national economic development. However, the main activities of the manufacturing subsidiaries of reputable MNCs located in Vietnam often specialize in the final product assembly (final assembly schedule-FAS). Correlatively, some Vietnam’s domestic enterprises (VDEs) are engaged either in outsourcing, or become MNC suppliers, but their position in the SCs is unstable. In this article, synthesis methodology and framework of analysis were used to clarify the status of Vietnam’s suppliers and their limited power in buyer-supplier relationships and to make some recommendations that may be useful to related parties. The article also provides an overview of the unprecedented impacts of the COVID-19 pandemic on Vietnamese businesses, and the appropriate responses to reshape and strengthen SCs for production in VietNam.